2011
DOI: 10.1007/s11892-011-0209-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic and Regulatory T Cells in Type 1 Diabetes: Losing Self-Control, Restoring It, and How to Take the Temperature

Abstract: The central role of T cells in type 1 diabetes pathogenesis is well established, but these cells continue to pose numerous challenges in understanding their dynamics and in following their modifications. Important progress has been recently made in pinpointing some novel antigens targeted by pathogenic T cells and the epitope sequences recognized. Studies on the interplay between effector T cells, their regulatory counterparts, and cells of the innate immune system have unraveled novel pathways and may inspire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…T cells reactive to several islet autoantigens have been indentified in humans . Although it is generally accepted that T cells have a role during the disease process, the possible function of B cells and autoAb in T1D in humans has not been completely resolved.…”
Section: T and B Cells Are Necessary For T1d Developmentmentioning
confidence: 99%
“…T cells reactive to several islet autoantigens have been indentified in humans . Although it is generally accepted that T cells have a role during the disease process, the possible function of B cells and autoAb in T1D in humans has not been completely resolved.…”
Section: T and B Cells Are Necessary For T1d Developmentmentioning
confidence: 99%
“…Furthermore, results from animal models and clinical studies have clearly demonstrated that Treg deficiency and/or functional defects might contribute to the pathophysiology of aplastic anemia [25] and idiopathic thrombocytopenia [26,27], of autoimmune diseases like type-1 diabetes [28,29], multiple sclerosis [30], rheumatoid arthritis [30], as well as organ transplant rejection [31,32] and thus represent potential targets of Treg cell therapy (Table 3).…”
Section: Ex Vivo Expansion [31] Kidney-transplant Rejectionmentioning
confidence: 99%
“…It appears that in nondiabetic individuals, potentially pathogenic T cells are held in check by various Tregdependent mechanisms. T1D may develop due, at least in part, to a defect (either functional or numerical) in the Treg repertoire or resilience of islet-reactive T cells to be suppressed[71]. Due to side effects associated with long-term generalized immunosuppression, the induction and maintenance of long-lasting tolerance specific to islet Ags remains a major focus for T1D clinical trials.…”
mentioning
confidence: 99%